Myofibroma of the tongue: A case report of a rapidly growing tumor and review of characteristics. Issue 3 (May 2015) - Saleh, Ramy R.; Rodic, Stefan; Musharrafieh, Umayya; Jabbour, Mark N.; Sabri, Alain
Abstract Solitary myofibroma of the tongue is an uncommon condition reported in 36 cases worldwide in the English literature. Herein, we present the first case of tongue myofibroma diagnosed at the American University of Beirut-Medical Center (Lebanon), found in a 50-year-old female with no evident risk factors or associated co-morbid conditions. The tumor was well-circumscribed, associated with pain, exhibited rapid growth and showed a distinct biphasic pattern upon staining. The unique clinical presentation and the histological findings of this rare tumor are presented and compared with previously reported cases. A review of the literature was used to evaluate this lesion's demographic characteristics using 16 cases, while nine detailed cases were used to determine a general pathological phenotype. We aimed to emphasize features that may express variability between lesions and revealed a possible bimodal distribution of tongue myofibroma occurring in infancy as well as middle-aged individuals. Physicians should include myofibroma in the differential diagnosis of tongue lesions regardless of age.